Comprehensive Analysis of Hospitality Service Management in The Digital Era - Cahaya Dewi, Komang Indah; Midun, Benediktha Aprilliani; Paschalia Karnoto, Delviola Stefani; Pebriyanti, Ketut Dinda; Natasha Wira, Ketut Nia; Tejawati, Kadek Liana; Candra Dewi, Made Kartika; Maharani, Ni Kadek Ayu; Santi Diwyarthi, Ni Desak Made (Westscience Press, 2024)
This research aims to study the implementation of service excellence management in the hospitality industry. Using a qualitative approach, data collection methods include in-depth interviews, participant observations, and literature studies. Research bias is minimized through data triangulation techniques. The results of the study found that service excellence management is dynamically evolving in the present era. Hotels are striving to keep up with digital technology developments by engaging in both service implementation and hotel product marketing. Challenges and obstacles lie in human resource skills, technological readiness, and changes in guest preferences.